The effect of alloying elements in sintered-recycle steel compaction - Mohd Fauzi Jaafar (Universiti Malaysia Perlis, 2008)
Effects of alloying elements in the sintered-recycle steel compaction were studied using powder metallurgy technique. High-energy milling technique was used to crush and mill the waste steel chip in the form of spiral and thin to become powder by using a planetary ball mill. The alloying elements used in this project are chromium and nickel. The alloying element powders are mixing together according to weight percent of AISI 403, AISI 410 and AISI 414 stainless steel. The recycled steel compaction sintered in argon atmosphere at two different sintering temperatures. The higher sintering temperature produced the better mechanical properties. The addition of chromium and nickel causes improvement in the mechanical properties of steel compaction. Particle shape of raw and alloying powders and surface morphology of stainless steel was studied by using SEM. The particle size distribution is measured by using Malvern Mastersizer 2000 machine and was performed by curvatures. The porosity and density is determined from the water displacement method based on Archimedes principle. The density of AISI 414 is highest followed by AISI 410 and the lower density obtained in AISI 403. The hardness measurement the show AISI 414 has the highest hardness compared to AISI 410 and AISI 403.